Evaluation of malnutrition risk of inpatients in a research and training hospital: A cross-sectional study - İSLAMOĞLU, AYŞE HÜMEYRA; GÜNEŞ, FATMA ESRA; SABUNCULAR, GÜLEREN; ÇELİK, ZEHRA MARGOT (ELSEVIER, 2021)
Background & aims: Malnutrition is one of the most important factors affecting the prognosis of inpatients. The aim of this study is to determine the malnutrition risk of hospitalized patients and to examine the relationship between the presence of malnutrition and other parameters. Methods: The study included 162 inpatients over the age of 25 who were staying in the hospital's internal medicine service for 7 days or more and who volunteered to participate in the study. A demographic-information questionnaire, consisting of 5 sections, a 24-h food recall record, NRS-2002, NRI and Beck Depression Inventory was given to patients during bedside interviews. After obtaining the necessary permission, the anthropometric measurements and biochemical parameter values of the patients were taken from their files. All statistical analyzes were performed by researchers with the SPSS package program. Results: Of 162 patients (48.8% female, 51.2% male), 24.7% were at risk for malnutrition according to NRS-2002 and 66.7% of the patients were not depressive, based on the Beck Depression Inventory scale. The malnutrition risk was higher (60.0%) in patients who had been hospitalized for more than 15 days (p = 0.010). The majority of those with malnutrition had no problems preventing them from eating (32.5%), were found to be not depressive (52.5%) and were in the normal range of body mass index (57.5%) (p = 0.002, p = 0.034, p = 0.001; respectively). Nutrient intake was lower in patients with a higher malnutrition risk, but the difference was insignificant (p > 0.05). Albumin levels (p = 0.028) and total protein levels (p = 0.015) were significantly lower in patients who were at risk of malnutrition. While overweight patients showed higher levels of serum albumin (p < 0.001), CRP levels were found to be lower in overweight patients (p < 0.001). Conclusions: It was found that the majority of patients with malnutrition were in the normal range for BMI. Nutritional intake and biochemical parameters should be followed closely in patients who are at risk of malnutrition. Depression can be a cause for insufficient nutrition and should be evaluated, particularly in patients whose length of hospital stay is greater than 7 days. (C) 2020 European Society for Clinical Nutrition and Metabolism. Published by Elsevier Ltd. All rights reserved.
Keywords: Malnutrition; Depression; NRS-2002; Nutritional status